Report on seven focus groups conducted for the achieving innovation in central government organisations report - Bartholomeou, P; Bastow, S; Dunleavy, P; Margetts, H; Pearce, O; Tinkler, J (LSE Public Policy Group and Oxford Internet Institute, 2006)
1. During September and October 2005, a team from the LSE Public Policy Group carried out seven focus groups as part of the Achieving Innovation in central government organisations (London: The Stationary Office, 2006) HC 1447 Session 2005-2006, published 25 July 2006. All the focus groups took place at the London School of Economics in Central London. The seven groups were made up of: project manager level civil servants; mid-level civil servants; and senior civil servants. We also ran four comparative focus groups with: management consultants and IT practitioners, both groups had some experience of working with government; a general business group; and local authority chief executives or senior staff. 2. These focus groups were undertaken in order to feedback some early results from a survey we had sent out to 126 central government organisations. The survey asked central government organisations to nominate an innovation and then provide details about its origins, triggers, costs, barriers and impacts. More details on this, and the full report, can be downloaded free from the Publications pages of www.nao.gov.uk or from the site at www.GovernmentOnTheWeb.org.